¿Al borde de la desintegración? Nación, conflictos internos y política en Bolivia, 1825-1829 - Soux, María Luisa (Anuario de Historia de América Latina, 2021)
The purpose of this article is to analyze the relationship between political projects and discourses with the difficult process of consolidation of the Republic of Bolivia in the first four years of independent life. Despite the consensus for the creation of an independent republic in 1825, in the following years different positions emerged on issues such as citizenship, religion and state organization, with the issue of presidency for life being central. By 1828, opposition to the Bolivarian project led to a crisis that manifested itself in the presence of a Peruvian army in Bolivia, the expulsion of Colombian troops and the end of the Sucre government.